2020
DOI: 10.3389/fphar.2020.547966
|View full text |Cite|
|
Sign up to set email alerts
|

Pinocembrin Decreases Ventricular Fibrillation Susceptibility in a Rat Model of Depression

Abstract: Background: Depression is associated with the increased risk of mortality and morbidity and is an independent risk factor for many cardiovascular diseases. Depression may promote cardiac arrhythmias, but little is known about the mechanisms. Pinocembrin mitigated depressive-like behaviors and exhibited cardioprotective effects in several models; however, whether pinocembrin benefits ventricular arrhythmias in depression models has not been elucidated. Thus, this study was to evaluate the effects of pinocembrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Wang et al (2020) have found pinocembrin could mitigate depressive-like behaviors induced by inhibiting the cell apoptosis and the pro-inflammatory factors expression). Besides, it is showed pinocembrin may decreases ventricular fibrillation susceptibility in the depression model (Ye et al , 2020), indicating that it has multiple therapeutic targets and application prospects in the future. In line with these perspectives, further studies are needed to determine the exact origins and mechanisms in the antineuroinflammatory effect of pinocembrin.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2020) have found pinocembrin could mitigate depressive-like behaviors induced by inhibiting the cell apoptosis and the pro-inflammatory factors expression). Besides, it is showed pinocembrin may decreases ventricular fibrillation susceptibility in the depression model (Ye et al , 2020), indicating that it has multiple therapeutic targets and application prospects in the future. In line with these perspectives, further studies are needed to determine the exact origins and mechanisms in the antineuroinflammatory effect of pinocembrin.…”
Section: Discussionmentioning
confidence: 99%
“…QT interval, QTc interval, and Tpeak–Tend interval are markers of cardiac arrhythmia. Both prolonged QT and QTc [ 14 ] and shortened QT interval and QTc [ 15 ] are associated with malignant ventricular arrhythmia (VAs). Prolonged Tpeak–Tend is associated with an elevated arrhythmic risk [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The OFT was performed to analyze the movement of the rats as described previously ( 14 ). Briefly, the rats were placed separately in the middle of an open field (100 cm × 100 cm × 50 cm), and the behavior of the rats was recorded and analyzed by a video-tracking system (EthoVision 3.0, Noldus) for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Pinocembrin decreased the risk of ventricular arrhythmias and reduced the myocardial infarction area in the myocardial ischemia-reperfusion rats ( 12 ). Pinocembrin decreased AF susceptibility in the myocardial infarction rats ( 13 ) and reduced ventricular fibrillation (VF) susceptibility in the depressed rats ( 14 ). However, whether pinocembrin alleviates AF susceptibility in the depressed rats is not clear.…”
Section: Introductionmentioning
confidence: 99%